Fly ash adsorbent for ph improvement and manganese reduction in acid mine drainage - Nurlela; Agustina, Tuty Emilia; Arita, Susila; Bahrin, David; Gayatri, Rianyza (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2025)
Metal solid waste from coal combustion (fly ash) is abundant in Indonesia, as an effective and economical adsorbent in neutralizing acid mine drainage (AMD). Given that the continuous utilization of coal produces environmental challenges in the form of AMD containing acid residues and heavy metals such as manganese (Mn), an appropriate treatment solution is required. The adsorption method was chosen due to its simplicity, cost effectiveness, and ability to remove heavy metal pollutants. The purpose of this research is to characterize fly ash before and after heating by SEM and XRD analysis, and evaluate the effect of fly ash physical activation temperature by heating at 100oC and 200oC for an interval of 60 minutes on the characteristics and adsorption ability of fly ash. In addition, this study also evaluated the effectiveness of the adsorbent mass (fly ash before heating and after heating) in increasing pH and reducing Mn concentration in AMD so that it meets the quality standards of Class 1 river water. The results obtained from this study show a fundamental difference in the properties of fly ash before and after heating. Based on BET analysis, the physical activation process resulted in pore enlargement (0.196 nm) and increased surface area of the adsorbent (0.847 m2/g), which significantly affected its binding capacity to solutes (adsorption capacity). The application of fly ash as an adsorbent showed the ability to increase the pH value of acid mine drainage towards neutral conditions. The process of reducing heavy metal ions Mn by using 50 g of fly ash heating at 100oC and 200oC, resulted in a removal percentage of 94.74% and 98.44%. It is hoped that this research can provide innovative and sustainable AMD treatment and increase the use value of fly ash waste.